2022
DOI: 10.3390/antibiotics11070858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Carbapenemase-Phenotypic Detection Methods and Emergence of Diverse VIM and GES Variants among Pseudomonas aeruginosa Isolates in Tunisia

Abstract: Background: Since 2012, few reports on the molecular epidemiology of Pseudomonas aeruginosa were reported in Tunisia. Objectives: This study aimed to evaluate carbapenem-resistance determinants and molecular epidemiology and to compare the carbapenemase-phenotypic detection methods of multidrug-resistant P. aeruginosa isolates. Methods: During a period of four years (2014 to 2017), all imipenem-ceftazidime-resistant P. aeruginosa isolates were retrospectively selected at the microbial laboratory of Charles Nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Moreover, four isolates (7%) were VIM-2 MBL producers. This result aligns with the recent studies reporting the detection of GES-5 and VIM-2 in the CRPA of Tunisia [ 30 , 31 ], and it is worth mentioning that this GES-5 prevalence in CRPA might be a sign of the start of the expansion of these strains in Tunisia. On the other hand, the predominance of VIM-2 among P. aeruginosa was previously revealed in studies performed in Tunisia [ 25 , 28 , 29 , 31 ] and in other countries such as the United Arab Emirates [ 34 ], Spain [ 32 , 43 , 44 , 48 ], Russia, the United States [ 14 ], Lebanon, and Egypt [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, four isolates (7%) were VIM-2 MBL producers. This result aligns with the recent studies reporting the detection of GES-5 and VIM-2 in the CRPA of Tunisia [ 30 , 31 ], and it is worth mentioning that this GES-5 prevalence in CRPA might be a sign of the start of the expansion of these strains in Tunisia. On the other hand, the predominance of VIM-2 among P. aeruginosa was previously revealed in studies performed in Tunisia [ 25 , 28 , 29 , 31 ] and in other countries such as the United Arab Emirates [ 34 ], Spain [ 32 , 43 , 44 , 48 ], Russia, the United States [ 14 ], Lebanon, and Egypt [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the successful worldwide spread of high-risk clones of P. aeruginosa poses a threat to global public health that needs to be studied and managed. However, few reports have been conducted on the molecular epidemiology or molecular typing of CRPA in Tunisia [ 29 , 30 , 31 ]. The aim of the present study was to analyze the characteristics of clinical CRPA isolates recovered from the Military Hospital of Tunis, including their antimicrobial resistance, integrons, virulence factors, and molecular typing.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our study showed GES as the most encountered carbapenemase gene in P. aeruginosa . This was also found in other studies, conducted in Iran, Tunisia, Egypt and Japan [ 41 , 42 , 43 , 44 ]. A recent review on the frequency of carbapenemase genes showed the high prevalence of bla VIM and bla IMP in Romania [ 45 ].…”
Section: Discussionsupporting
confidence: 87%
“…This is the first VIM-GES-CRPA outbreak reported in the US and globally; no other confirmed or suspected outbreaks have been documented. However, several genomic analysis studies have identified the co-expression of VIM and GES genes, of differing variants, in isolated cases in several countries [28][29][30][31][32][33] (Table 1). Although this previous outbreak was caused by a different P. aeruginosa strain, it demonstrates the bacteria's propensity to cause nosocomial infections.…”
Section: Comparison With Past Outbreaksmentioning
confidence: 99%
“…Unfortunately, there is limited data regarding global VIM-GES-CRPA prevalence, and although isolated confirmed cases have occurred in several countries, there is likely underreporting [28][29][30][31][32][33]. Ezricare eyedrops were marketed in the US [41], however, the outbreak source could be certain eyedrop ingredients or manufacturing equipment.…”
Section: Critical Analysismentioning
confidence: 99%